Helicobacter mastomyrinus infection induces autoimmune hepatitis in mice - Liqi Zhu; Yuanyuan Liang; Linghan Yang; Qihui Yang; Jun Yin; Tao Wang; Xiangming Xu; Quan Zhang (Journal of Translational Autoimmunity)
Abstracts: Background: Autoimmune hepatitis (AIH) is a chronic progressive liver disease caused by the immune system mistakenly attacking its own hepatocytes. The role of the gut microbiome in the pathogenesis and progression of AIH is of considerable significance. However, the dearth of suitable animal models has significantly constrained advancements in the pathogenesis and the development of therapeutic strategies for AIH. Helicobacter mastomyrinus (H. mastomyrinus, Hm) is a potentially zoonotic pathogenic microorganism capable of causing diseases of the enterohepatic system in rodent laboratory animals. Nevertheless, research on its role and mechanisms in causing liver disease is severely limited. Methods: In this study, male BALB/c mice were infected with Hm isolate Hm-17, and were sacrificed at 4 w, 8 w, 14 w and 22 w after infection, respectively. The serum was collected for detecting a number of AIH indicators, including the aminotransferases level, IgG content and autoantibody level. Additionally, the liver tissue was examined for pathological analysis, fibrosis, bacterial content, and the distribution of immune cells. Results: It was observed that the infection initially caused focal necrotizing hepatitis and subsequently progressed to interface hepatitis with lymphocyte/plasma cell infiltration, as well as hypergammaglobulinemia and autoantibody reactions, predominantly to Anti-nuclear and anti-smooth muscle antibodies. Furthermore, as the infection persisted, the mice exhibited a progressive increase in liver fibrosis and mild steatosis. Despite the maintenance of a low level of Hm colonization in the liver, there was a notable infiltrate of macrophages, T and B lymphocytes. In particular, the inflammatory foci in the Hm-infected liver were highly enriched for IL17+ cells. Conclusion: The present study provides an animal model of immunological liver injury induced by Hm infection that exhibits main characteristics similar to those observed in AIH-1 patients. This model may serve as a novel animal model for the study of the pathogenesis and potential therapeutic strategies for human AIH.